The Gender Diversity Executive, Thin Capitalization, Capital Intensity on Tax Avoidance and Firm Value - Lestari , Veny Abidatul; Eny Maryanti; Biduri, Sarwenda (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2024)
Introduction/ Main Objectives: The purpose of this study is to ascertain how executive gender diversity, thin capitalization, and capital intensity affect tax evasion and firm value. Background Problems: The main source of income for the Indonesian government, which is used for national development, is taxes. Taxes, however, can be a cost that lowers business profitability because they fluctuate by a company's performance. Research Methods: Quantitative research methodology is employed. Purposive sampling was used in this study to select a sample of manufacturing firms in the food and beverage subsector that were listed on the Indonesia Stock Exchange between 2018 and 2021. 43 businesses provided samples. Using SPSS 26 as the analysis tool, multiple linear regression was used for this study. Findings / Results: The findings indicate that whereas thin capitalization and capital intensity have a substantial impact on tax avoidance, gender diversity has no influence. Thin capitalization and capital intensity have a significant effect on firm value, while gender diversity in the executive has no effect. Conclusion: The research implies that management should take them into account when carrying out legal tax avoidance strategies and that financial managers should pay attention to non-financial factors that could affect a company's worth.